Linezolid-Induced Glossitis and Papillitis in Orthopedic Patients With Postoperative Infection: A Case Report - Ryan J. Blake; Benjamin M. Frye; Allison M. Lastinger (Case Reports in Infectious Diseases)
Linezolid, an oxazolidinone antibiotic, is commonly used to treat Gram-positive skin infections and has additional off-label success in treating bone and soft tissue infections. Linezolid has been associated with adverse effects, particularly those that are hematologic and neurologic in nature. However, we present three orthopedic patients who developed oral pain and swelling of the circumvallate papillae after a 10-day course of linezolid therapy, without the characteristic color changes associated with black hairy tongue as previously reported in the literature. All three patients were treated for superficial infections, and none exhibited signs of drug toxicity or neutropenia. Adverse side effects emerged despite short-term linezolid use, contrasting with previously reported cases involving long-term therapy. While black hairy tongue has been associated with linezolid and other antibiotics, these cases represent the first reported instance of generalized glossitis and papillitis without discoloration or noticeable alterations in the anterior portions of the tongue. The absence of coinfections or concurrent medications likely to cause similar symptoms suggests a unique set of side effects potentially correlated with linezolid. This case series emphasizes the importance of monitoring for atypical oral symptoms in patients on short-term linezolid therapy and adds to the growing body of literature on the side-effect profile. Further investigation into the mechanism of these reactions is necessary to better guide clinical practice in managing antibiotic-related oral adverse effects.